The Role of Progressive Tax, Tax Sanctions, Tax Amnesty, and Mobile Samsat in Increasing Vehicle Taxpayer Compliance - Nuryansyah, Adha; Putra, Yananto Mihadi (Pelita : Jurnal Penelitian, Terapan dan Aplikatif, 2025)
Motor Vehicle Tax (PKB) is a major source of Regional Original Income (PAD) that contributes significantly to supporting regional development. Bogor Regency, with its high growth rate of motorized vehicles, faces serious challenges in improving motor vehicle taxpayer compliance. To address this, the local government has implemented various policies, including progressive taxes, tax sanctions, tax amnesty programs, and mobile vehicle tax office services. This study aims to analyze the effect of progressive taxes, tax sanctions, motor vehicle tax amnesty programs, and mobile vehicle tax office services on motor vehicle taxpayer compliance in Bogor Regency. The research method used is quantitative with a multiple linear regression approach. Primary data were obtained through questionnaires distributed to motor vehicle taxpayers in Bogor Regency, while secondary data were obtained from documentation from relevant agencies. The results show that tax sanctions and mobile vehicle tax office variables have a positive and significant effect on motor vehicle taxpayer compliance. Conversely, progressive taxes and tax amnesty programs do not have a significant effect on the level of compliance. These findings indicate that the existence of strict sanctions and easy access to tax services through mobile vehicle tax office services are more effective in encouraging taxpayer compliance than the application of progressive rates or incentives in the form of fine waivers. The implication of this research is the need to strengthen public service policies that are oriented towards convenience, proximity, and legal certainty, so that taxpayer compliance can be increased sustainably and provide optimal contributions to the Regional Original Income of Bogor Regency.